Regulation and the evolution of corporate boards: monitoring, advising or window dressing? - Eric Helland; Michael Sykuta (Claremont McKenna College, Department of Economics, 2002)
It is generally agreed that boards are endogenously determined institutions that serve both an oversight and advisory role in a firm. While oversight role of boards has been extensively studied relatively few studies have examined the advisory role of corporate boards. In this study we examine the participation of political directors on the boards of natural gas companies between 1930 and 1998. We focus on the 1938, and 1954 regulation and 1986 partial deregulation of the natural gas industry. Using datasets covering the period from 1930 to 1990 and 1978 to 1998, we test whether regulation and deregulation altered the composition of companies' boards as the firms' environment changed. In particular, did regulation cause an increase and deregulation a decrease, in the number of political directors on corporate boards? We find evidence that the number of political directors increases as firms shift from market to political competition. Specifically the regulation of natural gas is associated with an increase in the number of political directors and the deregulation is associated with a decrease in the number of political directors on boards.
Keywords: 330; Vorstand; Aufsichtsrat; Regulierung; Staatliche Einflussnahme; Gaswirtschaft; USA